The physics of organic superconductors and conductors - Lebed, Andrei G. (Springer, 2017)
pt. 1. Historical surveys -- pt. 2. General reviews -- pt. 3. Unusual properties of a metallic phase -- pt. 4. Field-induced spin(charge)-density wave phases -- pt. 5. Unconventional superconducting properties -- pt. 6. Electron correlations in organic conductors.